THE ROLE OF C-REACTIVE PROTEIN AND POLYMORPHISMS OF ITS CANDIDATE GENES IN THE DEVELOPMENT OF IN-HOSPITAL CARDIOVASCULAR COMPLICATIONS IN PATIENTS AFTER CORONARY BYPASS SURGERY - O. L. Barbarash; Yu. V. Bayrakova; A. V. Ponasenko; S. V. Ivanov; Ya. V. Kazachek; M. V. Khutornaya; E. D. Bazdyrev; O. V. Gruzdeva; A. A. Kuzmina; L. S. Barbarash (Российский кардиологический журнал, 2015)
Aim. To assess the prognostic significance of preoperation C-r.p. concentration and polymorphic site of the gene CRP (rs3093077, rs1130864, rs1205) for the development of early cardiovascular complications after direct myocardial revascularization.Material and methods. Totally 249 patients studied with CHD, underwent coronary bypass surgery (CBG). Concentration of C-r.p. was assessed with high-sensitive immune-turbidimetric method, genotyping was done by 96-hole format via TaqMan method, before CBG.Results. The risk of perioperational CVC increased in presence of such factors as age more than 65 y. o. (р=0,037), preoperational C-r.p. concentration higher than 5 mg/mL (р=0,026), homozygous genotype GG in promoter region of CRP gene (rs3093077) (c2 =9,08, р=0,0011) within all other conditions different (presence or absence of atrial fibrillation (AF), diabetes mellitus (DM) 2 type, duration of hypertension anamnesis (AH). In patients older than 65 y. o. the CVC risk increased almost 3 times: OR=2,8 (95% CI=1,07-7,34), and in serum concentrations of C-r.p. more than 5 mg/mL — two and a half times: OR=2,5 (95% CI=1,11-5,77). The carriage of genotype GG rs3093077 СRP increases the risk of CVC in in-hospital period of CBG for more than 2 times.Conclusion. For prediction of CVC in CBG it is necessary to evaluate not only clinical and anamnestic characteristics of a patient, but also the level of preoperation CRP, and genetic polymorphisms of their genes.